Activity profile in elite Polish soccer players - Andrzejewski, M.; Pluta, B.; Konefal, M.; Konarski, J.; Chmura, J.; Chmura, P. (Research in Sports Medicine, 2019)
The aim of the present study was to determine and characterize the activity of male Polish Premier League soccer players during elite-level matches, depending on playing position, activity intensity range, and match period. The study sample comprised 1178 players. Amisco Pro® was used to track the match activity players. Statistical analysis of the total distance covered by players revealed that the greatest distance was covered by central midfielders (11894 ± 765 m) and external midfielders (11751 ± 686 m). In terms of velocity, the greatest distance was covered by players in the V1 range (0 = V1 < 11 km · h-1, standing, walking), (7028 ± 294 m). The difference between the match periods was statistically non-significant, amounting to only 0.5%. As such they could prove useful for present and future comparisons between positions and represent the scientific basis for developing position-specific conditioning/training regimes for both clubs and individuals.